Longitudinal and Reciprocal Relationships Between Depression and Disability in Older Women Caregivers and Noncaregivers - Bacon, Kathryn L. (Gerontologist, 2016)
PURPOSE OF THE STUDY: Depressive symptoms and disability each increase the risk of the other, yet few studies have examined reciprocal associations between these conditions in a single study, or over periods longer than 3 years. These associations may differ in older caregivers due to chronic stress, health characteristics, or factors related to caregiving. DESIGN AND METHODS: Structural equation models were used to investigate relationships between depressive symptoms and disability over 3 interviews spanning 6 years among 956 older women (M = 81.5 years) from the Caregiver Study of Osteoporotic Fractures. Results were evaluated separately for 611 noncaregivers and 345 caregivers to a relative or friend. RESULTS: In noncaregivers, more depressive symptoms significantly predicted greater disability, whereas greater disability predicted increased depressive symptoms at the next interview in age-adjusted models. In contrast, there was not a significant relationship between depression and disability in either direction for caregivers. Further adjustment for body mass index and medical condition variables did not change these relationships. IMPLICATIONS: Caregivers did not exhibit longitudinal or reciprocal relationships between depressive symptoms and disability observed in noncaregivers. It is possible that older women caregivers are buffered by better physical condition or social interactions related to caregiving activities.